Bidirectional direct current-direct current converter for fuel cell and renewable energy hybrid systems - Kabalo, M.; Al-Durra, A.; Muyeen, S.M.; Simôes, M. (American Institute of Physics, 2015)
A bidirectional dc-dc power converter is an essential part of a HFCEV (Hybrid Fuel Cell Electric Vehicle) and renewable energy hybrid system. This paper presents a new bidirectional dc-dc power converter for HFCEV and renewable energy hybrid systems. The proposed converter is called four phases floating interleaved boost converter. Two control strategies of the dc-bus voltage are discussed. In the first one, a dual loop with linear current and voltage controllers is developed, based on the frequency response of the system. In the second one, the linear current controller is replaced by a non-linear sliding mode current controller, to improve the system performance from the robustness point of view. The non-linear sliding mode controller is designed based on the average model of the proposed topology. The proposed control strategies have been validated by simulation and experimental results.